Organization of olfactory centres in the malaria mosquito Anopheles gambiae - Olena Riabinina (Nature Portfolio, 2016)
Mosquitoes use olfactory cues to locate their host. Here, Riabinina et al. use genetic labelling of olfactory receptor neurons in the malaria vector Anopheles gambiaeto show that these neurons project to the antennal lobe, a known insect olfactory centre, and the subesophageal zone, a region previously linked to gustatory processing.